2019
DOI: 10.3389/fphar.2019.00067
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Kalanchoe mortagei and K. fedtschenkoi Against ESKAPE Pathogens

Abstract: Plants in the genus Kalanchoe (Family: Crassulaceae) are used in traditional medicine throughout the tropics for treating a variety of conditions. Two species, Kalanchoe mortagei and K. fedtschenkoi, have established ethnobotanical usage but have been neglected in previous research concerning their potential bioactivity. Here, we provide a thorough review of the reported antimicrobial activities of Kalanchoe genus and evaluate the in vitro antibacterial effects of two previously unexplored species against a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…The antimicrobial activity attributed to Bryophyllum extracts was shown to present a high effectiveness against a wide range of both bacterial and fungal activities. In this sense, hydroethanolic extracts from B. fedtschenkoi showed a strong inhibitory effect against different antimicrobial resistant strains from the ESKAPE complex, including both Gram-negative and Gram-positive bacteria [37]. Similarly, the bactericidal effect of B. crenatum leaf juice against Bacillus subtilis and Klebsiella pneumoniae was also reported, as well as high effectiveness of methanol extracts from B. pinnatum to Gram-positive bacteria [34].…”
Section: Species Ethnobotanical Uses Plant Organ Locationsmentioning
confidence: 91%
“…The antimicrobial activity attributed to Bryophyllum extracts was shown to present a high effectiveness against a wide range of both bacterial and fungal activities. In this sense, hydroethanolic extracts from B. fedtschenkoi showed a strong inhibitory effect against different antimicrobial resistant strains from the ESKAPE complex, including both Gram-negative and Gram-positive bacteria [37]. Similarly, the bactericidal effect of B. crenatum leaf juice against Bacillus subtilis and Klebsiella pneumoniae was also reported, as well as high effectiveness of methanol extracts from B. pinnatum to Gram-positive bacteria [34].…”
Section: Species Ethnobotanical Uses Plant Organ Locationsmentioning
confidence: 91%
“…K. fedtschenkoi extract exhibited growth inhibition against two Gram-negative sp. A. baumannii (CDC-33) and P. aeruginosa (AH-71) as well as Gram-positive S. aureus [14]. Extract in other studies with S. aureus have always shown growth inhibition with the exception of the poor performance of a hexane fraction tested [15].…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus spp. and some air borne and food borne pathogenic bacteria at alarming stage (Bhatti et al, 2019;Richwagen et al, 2019;Chatham-Stephens et al, 2019;Mehboob and Abbas 2019;Naz & Pasha 2019;Irum et al, 2019). According to the published data, the mortality rate is about 0.7 million worldwide due to antimicrobial resistance pathogens, which will raise 10 million by 2050 (de Kraker et al, 2019) The data reported by Center of Disease and Control showed about 23,000 mortality rates due to infection caused by antimicrobial resistance annually (Lim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%